BCS Model Hamiltonian of the Theory of Superconductivity as a Quadratic Form - Petrina, D.Ya. (Український математичний журнал, 2004)
Bogolyubov proved that the average energies (per unit volume) of the ground states for the BCS Hamiltonian and the approximating Hamiltonian asymptotically coincide in the thermodynamic limit. In the present paper, we show that this result is also true for all excited states. We also establish that, in the thermodynamic limit, the BCS Hamiltonian and the approximating Hamiltonian asymptotically coincide as quadratic forms. M. M. Боголюбов довів, що середні енергії на одиницю об'єму основних станів для гамільтоніана БКШ та апроксимуючого гамільтоніана у термодинамічній границі асимптотично збігаються. У даній роботі показано, що цей результат має місце і для усіх збуджених етапів. Водночас встановлено, що гамільтопіан БКШ та апроксимуючий гамільтоніан у термодинамічній границі асимптотично збігаються як квадратичні форми.